Hysterosalpingography in infertility - Bagaswoto Poedjomartono Bagaswoto Poedjomartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
Hysterosalpingography is performed by injecting contrast media into the uterus to visualize the uterine cavity and Fallopian tubes. Water-soluble contrast media are used in these examinations. Hysterosalpingographic examination is very important for the diagnosis of infertility and some gynecologic abnormalities.Between January-December 1981 hysterosalpingography had been performed in 79 cases of primary infertility, 28 cases of secondary infertility and 3 cases with abortion history. The hysterosalpingogram demonstrated that 23.64% of all cases were bilateral non-patent and 21.8% unilateral non-patent. Hydrosalpinx was found in 22 cases, 17 cases with bilateral or unilateral non-patent tubes and 5 cases with patent ones. Ten cases showed paratubal filling assosiated with patent and non-patent tubes.Key Words: hysterosalpingography - hydrosalpinx - infertility - contrast media - Fallopian